2014
DOI: 10.1007/s11743-014-1590-5
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Surface‐Active Behavior of New Fluorinated Hyperbranched Polymer

Abstract: In this article, a series of novel hyperbranched fluorinated polymer with polyglycerol (PG) as the hydrophilic core and poly(2,2,2‐trifluoroethyl methacrylate) (PTFEMA) as solvophobic arms were synthesized. When the atom transfer radical polymerization was carried out using N,N‐dimethylformamide (DMF) as the solvent, [M]/[I] ratio of 200, and [CuBr]/[NBr] ratio of 0.1 at 30 °C, controlled polymerization was achieved. The surface active properties of the polymer at the dimethyl sulfoxide (DMSO)/air and chlorofo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
(52 reference statements)
0
1
0
Order By: Relevance
“…Chen et al [35] found that the aggregation behavior of X-shaped block copolymers at air/water interface can be changed by the variation of the block sequence or temperature. Fluorinated copolymers, especially the fluorinated acrylate copolymers, are excellent choice for design weakly amphiphilic diblock copolymers due to hydrophobicity and high surface activity at air/water interface [8,[36][37][38][39][40][41]. Zhu et al [42] examined the formation of various PVDF Langmuir films.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al [35] found that the aggregation behavior of X-shaped block copolymers at air/water interface can be changed by the variation of the block sequence or temperature. Fluorinated copolymers, especially the fluorinated acrylate copolymers, are excellent choice for design weakly amphiphilic diblock copolymers due to hydrophobicity and high surface activity at air/water interface [8,[36][37][38][39][40][41]. Zhu et al [42] examined the formation of various PVDF Langmuir films.…”
Section: Introductionmentioning
confidence: 99%